Katutubo directory. (Manila Global Indigenous Cultural Olympics Summit GICOS, 1996)
"This directory, presented as a supplement to the program of the 1996 global Indigenous Summit in Manila, provides a basic descriptive list of indigenous cultural communities in the Philippine Archipelago. All data were contributed by the Office for Northern cultural communities, and the Office on Muslim Affairs."
This directory, presented as a supplement to the program of the 1996 Global Indigenous Peoples Summit in Manila, provides a basic descriptive list of indigenous cultural communities in the Philippines Archipelago. All data were contributed by the Office for Northern Cultural Communities, and the Office on Muslim Affairs.
Keywords: Ethnology -- Philippines -- Directories; Indigenous peoples -- Philippines -- Directories